Pijat Akupresure untuk Mengurangi Nyeri Dismenore Primer pada Remaja Putri di SMPN 10 Penajam Paser Utara - wahyuni, sry; datuarrang, esther; cahyaningrum (Universitas Ngudi Waluyo, 2023)
Data from WHO obtained an incidence of 1,769,425 people (90%) of women who experience dysmenorrhea, 10%-15% of whom experience severe dysmenorrhea. Dysmenorrhea is pain before or during menstruation, occurring on the first day to several days of menstruation. Dysmenorrhea can have various unfavorable impacts on adolescent girls. These impacts include disrupted activities, limited physical activity, social isolation, poor concentration, absenteeism in the teaching and learning process at school and class, loss of concentration at school, inability to do homework, limitations in sports activities, limitations to go out with friends. Acupressure is the science of healing by doing massage at certain points, this science comes from China which has existed for more than 500 years. Community service is carried out in 3 stages, namely: Stage 1 Selection of adolescent girls who are willing to get acupressure massage to reduce pain. Stage 2: Conducting socialization and giving acupressure massage to reduce pain during dysmenorrhea. This community service activity was attended by 20 respondents consisting of 7th, 8th, and 9th grade students of SMPN 10 Penajam Paser Utara. From the results of univariate analysis before being given counseling to 20 respondents, 18 (90%) respondents had a sufficient level of knowledge and 2 (10%) respondents had a lack of knowledge and after counseling the results obtained from 20 respondents there were 10 (50%) respondents had a good level of knowledge, 10 (50%) respondents had a sufficient level of knowledge. From the results obtained after counseling there is an increase in respondents' knowledge of the material provided. Abstrak Data dari WHO didapatkan kejadian sebesar 1.769.425 jiwa (90%) wanita yang mengalami dismenore, 10%-15% diantaranya mengalami dismenore berat. Dismenore adalah nyeri sebelum atau selama menstruasi, terjadi pada hari pertama sampai beberapa hari masa menstruasi. Dismenore dapat memberikan berbagai dampak yang kurang baik bagi remaja putri. Dampak tersebut meliputi aktivitas yang terganggu, keterbatasan aktivitas fisik, isolasi sosial, konsentrasi yang buruk, ketidakhadiran dalam proses belajar mengajar di sekolah dan kelas, kehilangan konsentrasi di sekolah, ketidakmampuan untuk pekerjaan rumah, keterbatasan dalam aktivitas olahraga, keterbatasan untuk keluar dengan teman. Akupresure merupakan ilmu penyembuhan dengan cara melakukan pijat pada titik - titik tertentu, ilmu ini berasal dari Tionghoa yang suda ada sejak lebih dari 500 tahun yang lalu. Pengabdian masyarakat dilaksanakan dalam 3 tahap yaitu : Tahap 1 Pemilihan remaja putri yang bersedia mendapatkan pijat akupresure untuk mengurangi nyeri. Tahap 2 : Melakukan sosialisasi dan pemberian pijat akupresure untuk mengurangi nyeri pada saat dismenore. Kegiatan pengabdian Masyarakat ini di ikuti 20 orang responden yang terdiri dari siswi kelas 7,8,dan 9 SMPN 10 Penajam Paser Utara. Dari hasil analisis univariat sebelum diberikan penyuluhan terhadap 20 responden terdapat 18 (90%) responden memiliki tingkat pengetahuan cukup dan 2 (10%) responden memiliki tingkat pengetahuan kurang dan sesudah dilakukan penyuluhan didapatkan hasil dari 20 responden ada 10 (50%) responden memiliki tingkat pengetahuan baik, 10 (50%) responden memiliki tingkat pengetahuan cukup. Dari hasil yang didapatkan setelah dilakukan penyuluhan terdapat peningkatan pengetahuan responden terhadap materi yang diberikan.